Tests employed in the psychometric validation of the Insulin Treatment Appraisal Scale (ITAS) in T2DM patients; a systematic review of the literature - Saba Rasheed; Anees ur Rehman; Zermina Tasleem; Marryam Azeem; Muhammad Fawad Rasool; Arifa Mehreen; Saleh Karamah Al-Tamimi (SpringerOpen, 2024)
Abstract Background Psychological Insulin Resistance (PIR) and negative perceptions regarding insulin treatment are noteworthy challenges in T2DM management, which hinder the timely initiation of insulin treatment. To get past these obstacles a reliable tool is required to evaluate patients' perspectives on insulin administration. Our study aims to conduct a comprehensive systematic review to evaluate the validity and reliability of different validation tests used in the psychometric validation of the ITAS in T2DM patients. Methods A literature search was carried out, using PubMed, Google Scholar, EMBASE, Cochrane Library and Science Direct. Only those studies assessing content validity, construct validity, concurrent validity, discriminant validity, internal consistency reliability (Cronbach' α), and items-total correlation were retrieved. Results A total of 14 studies illustrated the validity and reliability of ITAS in T2DM patients. Content validity results of S-CVI was 0.97, and I-CVI was 0.8-1.00. Construct validity with factor loading was greater than the threshold value of 0.3. The concurrent validity of ITAS vs. PAID, WHO-5, and SPI was 0.35 (P < 0.05), −0.14 (P < 0.05), and 0.80 (P < 0.001) respectively. The mean difference between insulin and non-insulin group was significant (P < 0.001) showing reliable discriminant validity. Reported results of Cronbach's α for the main scale (0.79-0.89), subscale-1 (0.72-0.9), and subscale-2 (0.61-0.89) showed "good to excellent" internal consistency reliability of ITAS. Item-total correlation results for the main scale, subscale-1, and subscale-2 were (0.40-0.82), (0.31-0.74) and (0.34-0.58) respectively. Test-retest reliability of ITAS was 0.571-0.87. Conclusions Study findings confirm the robustness of various validation tests utilized in the psychometric validation of ITAS in T2DM patients. ITAS is a well-validated and reliable tool for determining the perspectives, PIR, and changes in patients' perception over time and it can be used to overcome hurdles in the timely initiation of insulin treatment in T2DM patients.